2008
DOI: 10.4049/jimmunol.181.5.3232
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Role for the λ5 Nonimmunoglobulin Tail in Early B Lymphocyte Development

Abstract: Precursor BCR (pre-BCR) signaling governs proliferation and differentiation of pre-B cells during B lymphocyte development. However, it is controversial as to which parts of the pre-BCR, which is composed of Igμ H chain, surrogate L chain (SLC), and Igα-Igβ, are important for signal initiation. Here, we show in transgenic mice that the N-terminal non-Ig-like (unique) tail of the surrogate L chain component λ5 is critical for enhancing pre-BCR-induced proliferation signals. Pre-BCRs with a mutated λ5 unique tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Cells that have undergone a successful V to D-J recombination are selected, and the expression of the pre-BCR mediates their proliferative expansion [1,4,12,13,[25][26][27][28]. In mice lacking the surrogate light chain components, and thus unable to express the pre-BCR, this selection and expansion process fails to operate, resulting in the generation of fewer immature and mature B cells [1,[12][13][14]29].…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 99%
“…Cells that have undergone a successful V to D-J recombination are selected, and the expression of the pre-BCR mediates their proliferative expansion [1,4,12,13,[25][26][27][28]. In mice lacking the surrogate light chain components, and thus unable to express the pre-BCR, this selection and expansion process fails to operate, resulting in the generation of fewer immature and mature B cells [1,[12][13][14]29].…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 99%
“…3 Expression of the pre-BCR represents a crucial checkpoint during B-cell development as this receptor controls pre-BII-cell development and the selection of the Ig repertoire. 4 The galectin-1 (GAL1) lectin and heparan sulfates, produced by the BM microenvironment, have been reported to bind to the pre-BCR, [5][6][7] and GAL1 was shown to promote pre-BCR clustering and signaling. 5 GAL1 binds to the SLC by a direct protein/protein interaction and to glycosylated integrins via the recognition of ␤-galactosides.…”
Section: Introductionmentioning
confidence: 99%
“…Both constitutive 12,13 and ligand-induced 3,14 signaling have been described. In the mouse, Bradl et al 4 and Vettermann et al 5 showed that pre-BCR binding to stromal cells required the N-terminal unique region of 5 (5UR) and stroma cell-associated HS. In humans, we reported that GAL1 binds to the 5UR by a protein/protein interaction but also to glycosylated integrins present on stromal and pre-B cells.…”
mentioning
confidence: 99%
“…However galectin-1 (GAL1) and heparan sulfates (HSs), produced by the BM microenvironment, have been described to bind to the pre-BCR. [3][4][5] Pre-BCR expression represents a crucial step in B-cell development as it controls pre-BII-cell proliferation and differentiation. 6 Pre-BCRs also mediate allelic exclusion at the IgH locus 7,8 and selection of the Ig chain repertoire, 9 leading to the counterselection of autoreactive Ig chains.…”
mentioning
confidence: 99%